Pharmacogenetics of tardive dyskinesia: a "movement" towards individualized therapy 2 - Basile, Vincenzo (Henry Stewart Talks, 2007)
Pharmacokinetics and TD: a look at the cytochrome P450 system, Oxidative stress and TD: a look at free radicals and the superoxide dismutase genes, Psychiatric pharmacogenetics as cleaner complex phenotypes, Neuroimaging in pharmacogenetics: towards even cleaner phenotypes, Complex traits and new statistical models for looking at multigene interactions with continuous variables, Recommendations for future studies: bringing pharmacogenetics from "Bench to Bedside" and from "Bedside back to Bench", Onward towards individualized pharmacotherapy
Archived at 2021/02/25